Pengaruh Teknologi Digital terhadap Budaya dan Identitas Global - Hadi Wijaya Halim; Chita Pradnya Paramitha; Karina Putri Adita; Arryan Jibril; Andi Faisal Bakti (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The development of digital technology over the past two decades has revolutionized human communication, social interaction, and the formation of both individual and collective identities in a global context. Digital media no longer merely function as communication tools but have become socio-cultural spaces that actively shape values, norms, symbols, and everyday practices. This phenomenon raises research questions regarding how cultural transformation and identity construction are influenced by the dominance of digital technology, as well as how social media and platform algorithms shape cultural visibility and digital identities. This study employs a qualitative approach through a critical narrative literature review, synthesizing theories of network society, mediatization, cultural globalization, digital capitalism, and digital identity. The analysis focuses on four key issues: cultural digitalization, the role of social media in identity formation, the emergence of hybrid identities, and platform power in determining cultural representation. Findings indicate that digital technology has ambivalent effects: it expands spaces for cultural expression, enhances public participation, and provides opportunities for marginalized groups to represent their identities; however, global platform dominance drives cultural homogenization, identity commodification, and inequitable symbolic representation. The novelty of this study lies in integrating a critical perspective on the influence of algorithms and digital capitalism in identity formation, which has rarely been addressed comprehensively in digital cultural studies. These findings offer theoretical contributions to media and cultural research as well as practical implications for understanding identity representation in the global digital era.